A material and preparation method for a high-performance ultra-thin 5G tower
By using zirconia/carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler and modified fiber components in 5G tower materials, the problems of large volume and heavy weight of existing materials have been solved, and high performance has been achieved. Lightweight, corrosion-resistant ultra-thin 5G tower material meets the needs of modern communication networks.
Patent Information
- Application Number
- CN202411455597.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Due to its large size, heavy weight and complex installation, existing 5G tower materials are difficult to meet the needs of modern communication network construction, especially in urban environments, which are difficult to meet the requirements of lightweight, corrosion resistance and easy processing.
High-performance ultra-thin 5G tower materials are prepared by blending zirconia/carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler, modified fiber components and graphene oxide hybrid nanoparticles with polyurethane. They are used to blend them with silane coupling agent. Hybrid nanozirconia and carbon fibers, titanium tetrachloride hydrolyzes in situ on the surface of hexagonal boron nitride, silane coupling agents combine coconut fibers and glass fibers, graphene oxide and aminolated nanosilicon dioxide The particles are hybridized to form materials with high strength, toughness and corrosion resistance.
It significantly improves the strength, toughness and corrosion resistance of the tower material, reduces weight, enhances structural stability and safety, reduces transportation and installation costs, improves construction efficiency, and has good electromagnetic shielding and environmental protection performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a material and a preparation method for a high-performance ultra-thin 5G pole tower. Background Art
[0002] With the rapid development and widespread application of 5G communication technology, the performance requirements for communication infrastructure are increasing, especially in urban environments. Traditional poles and towers are difficult to meet the needs of modern communication network construction due to their large size, heavy weight, complex installation and high cost. Therefore, the development of an ultra-thin 5G pole and tower made of new materials has become an urgent need in the industry. This kind of pole and tower not only needs to have excellent mechanical properties, such as high strength, high toughness, good wind pressure resistance, etc., to ensure the stable operation of communication equipment; at the same time, it also needs to meet the requirements of lightweight, corrosion resistance, easy processing, etc., to adapt to the compact space and complex environment of modern urban construction.
[0003] Composite fiber materials have shown great application potential in 5G pole tower manufacturing due to their light weight, high strength, corrosion resistance, fatigue resistance and other characteristics. In addition, the overall weight of composite fiber materials is relatively light, which can facilitate transportation and installation while reducing maintenance costs. Therefore, how to prepare new composite fiber materials that can meet the standards of the 5G pole tower industry has become a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0004] Technical issues solved
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a material and a preparation method for a high-performance ultra-thin 5G pole tower, which can effectively solve the problems of bulky pole tower materials, heavy weight and complex installation in the prior art.
[0006] Technical Solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A high-performance ultra-thin 5G pole tower material, the high-performance ultra-thin 5G pole tower material consisting of the following components: zirconium oxide / carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler, modified fiber component, graphene oxide hybrid nanoparticles and polyurethane;
[0009] The zirconium oxide / carbon fiber hybrid powder is prepared by hybridizing nano zirconium oxide and carbon fiber with a silane coupling agent KH-560;
[0010] The titanium dioxide modified hexagonal boron nitride filler is prepared by in-situ hydrolysis of titanium tetrachloride on the surface of hexagonal boron nitride;
[0011] The modified fiber component is prepared by composite modification of coconut shell fiber and glass fiber by silane coupling agent KH-550;
[0012] The graphene oxide hybrid nanoparticles are prepared by taking graphene oxide and amino-treated nano-silicon dioxide particles as raw materials.
[0013] Furthermore, the preparation method of the zirconium oxide / carbon fiber hybrid powder is:
[0014] S2.1, weigh 5g of nano zirconium oxide powder and disperse it in 100mL of anhydrous ethanol, add 30mL of silane coupling agent KH-560 after ultrasonic treatment, stir at 200r / min for 6h in a water bath at 60℃, wash by centrifugation with anhydrous ethanol, and dry to obtain the modified nano zirconium oxide powder;
[0015] S2.2. Weigh 0.2g of carbon fiber and disperse it in 100mL of anhydrous ethanol. After ultrasonic treatment, add 30mL of silane coupling agent KH-560. Stir at 200r / min for 6h in a water bath at 60℃, then add 2g of modified nano-zirconia powder. Continue stirring at the original speed for 6h, wash with anhydrous ethanol by centrifugation, and dry to obtain the zirconia / carbon fiber hybrid powder.
[0016] Furthermore, the operation method of ultrasonic treatment in S2.1 is ultrasonic dispersion at a frequency of 28 kHz for 30 min, the amount of anhydrous ethanol used for centrifugal washing in S2.1 is 100 mL, the operation method of drying treatment in S2.1 is drying in an oven at 55°C for 3 h, the operation method of ultrasonic treatment in S2.2 is ultrasonic dispersion at a frequency of 28 kHz for 30 min, the amount of anhydrous ethanol used for centrifugal washing in S2.2 is 150 mL, and the operation method of drying treatment in S2.2 is drying in an oven at 58°C for 3 h.
[0017] Furthermore, the preparation method of the titanium dioxide modified hexagonal boron nitride filler is:
[0018] S4.1. Weigh 1 g of hexagonal boron nitride and pour it into 20 mL of deionized water. After ultrasonic treatment, record it as a dispersion. Pour 1 mL of titanium tetrachloride into 30 mL of deionized water, stir magnetically for 30 minutes, then add the dispersion. Add sodium hydroxide solution dropwise to adjust the pH value to 6 and stir to react for 30 minutes. Then pour it into a hydrothermal reactor and heat it to 180°C for 10 hours. The result is recorded as a reaction product. During the reaction process here, titanium tetrachloride can be in-situ hydrolyzed on the surface of hexagonal boron nitride, thereby generating nano titanium dioxide on the surface of hexagonal boron nitride through in-situ polymerization.
[0019] S4.2. The reaction product is cooled to room temperature and then centrifuged to remove the filtrate. The precipitate is washed with deionized water and anhydrous ethanol in turn and dried in an oven at 50°C for 12 hours. The precipitate is ground through a 200-mesh sieve to obtain titanium dioxide-modified hexagonal boron nitride.
[0020] Furthermore, the operation method of ultrasonic treatment in S4.1 is ultrasonic dispersion at a frequency of 26kHz for 30 minutes, the rotation speed of magnetic stirring in S4.1 is 300r / min, the concentration of sodium hydroxide solution in S4.1 is 5mol / L, the rotation speed of stirring reaction in S4.1 is 200r / min, and the operation method of centrifugal treatment in S4.2 is centrifugation at a rotation speed of 5000r / min for 5 minutes.
[0021] Furthermore, the preparation method of the modified fiber component is:
[0022] S6.1, soaking the coconut shell fiber in a sodium hydroxide solution for 1 hour, filtering and removing the filtrate, washing with a hydrochloric acid solution for 3 times, then washing with deionized water until neutral, freeze-drying, and recording the modified coconut shell fiber. In the reaction process here, soaking the coconut shell fiber in a sodium hydroxide solution can remove the grease on the surface of the coconut shell fiber, and can also increase the roughness and specific surface area of the coconut shell fiber, so as to prepare for the subsequent reaction with the silane coupling agent KH-550;
[0023] S6.2. Weigh 5 mL of silane coupling agent KH-550 and disperse it in 95 mL of anhydrous ethanol to prepare a silane coupling agent dispersion. Then, mix the coconut shell fiber and the glass fiber in an equal weight ratio and record it as mixed fiber. Weigh 30-40 g of the mixed fiber and add it into 100 mL of the silane coupling agent dispersion. After soaking for 2 hours, filter and remove the filtrate. After drying, the modified fiber component is obtained.
[0024] Furthermore, the mass concentration of the sodium hydroxide solution in S6.1 is 2%, the mass concentration of the hydrochloric acid solution in S6.1 is 0.5%, and the operation method of the drying treatment in S6.2 is to place it in an oven at 40°C and dry it for 12 hours.
[0025] Furthermore, the preparation method of the graphene oxide hybrid nanoparticles is:
[0026] S8.1, weigh 72g of anhydrous ethanol, 8g of deionized water and 20g of 3-aminopropyltriethoxysilane, pour them into a flask, stir and mix, add 12-15g of nano-silica and stir to react, filter and remove the filtrate after the reaction is completed, wash with anhydrous ethanol and deionized water three times respectively, dry and grind through a 200 mesh sieve to obtain amino-modified nano-silica particles, in the reaction process here, the ethoxy group of 3-aminopropyltriethoxysilane will be hydrolyzed into active silanol group in the ethanol aqueous solution, and the silanol group can react with the hydroxyl group on the surface of the nano-silica to form a chemical bond, and the amino group of 3-aminopropyltriethoxysilane can couple with the nano-silica;
[0027] S8.2, weigh 1g of graphene oxide and disperse it in 300mL of deionized water to prepare a graphene oxide aqueous solution, then weigh 1g of amino-modified nano-silica particles and disperse them in 500mL of anhydrous ethanol, and drop the graphene oxide aqueous solution after uniform dispersion, and then use deionized water and anhydrous ethanol to filter and wash three times after ultrasonic treatment, and then grind through a 200-mesh sieve after drying, and the obtained particles are recorded as the particles to be hybridized;
[0028] S8.3. Weigh 3 g of the particles to be hybridized and disperse them in 500 mL of deionized water to prepare a suspension. Then, add a 0.1 g / mL sodium borohydride solution to adjust the pH value to 10-12. After stirring the reaction in a water bath at 80°C, wash it three times with deionized water. After centrifugal drying, the resulting product is graphene oxide hybrid nanoparticles.
[0029] Furthermore, the stirring and mixing operation method in S8.1 is stirring at a speed of 500r / min for 1h, the stirring reaction operation method in S8.1 is stirring at a speed of 500r / min for 1.5h, the drying treatment operation method in S8.1 is drying in an oven at 50°C for 2h, the uniform dispersion operation method in S8.2 is stirring at a speed of 500r / min for 10min, the dripping rate in S8.2 is 2 drops / s, the ultrasonic treatment operation method in S8.2 is ultrasonic dispersion at a frequency of 26kHz for 30min, the drying treatment operation method in S8.2 is drying in an oven at 55°C for 2h, the stirring reaction operation method in S8.3 is stirring at a speed of 300r / min for 2h, and the centrifugal drying operation method in S8.3 is first centrifuging at a speed of 5000r / min for 5min and then drying the precipitate in an oven at 55°C for 3h.
[0030] A method for preparing a material for a high-performance ultra-thin 5G tower, the preparation method comprising:
[0031] Weigh 200 parts by weight of polyurethane and pour it into an internal mixer. After heating to 180-190°C, add 0.5-1 parts by weight of zirconium oxide / carbon fiber hybrid powder, 0.5-1 parts by weight of titanium dioxide modified hexagonal boron nitride filler, 1-2 parts by weight of modified fiber components and 0.5-1 parts by weight of graphene oxide hybrid nanoparticles. After blending, take out and press into shape, and the result is the material for high-performance ultra-thin 5G pole towers.
[0032] Beneficial Effects
[0033] The present invention provides a material and a preparation method for a high-performance ultra-thin 5G pole tower. Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention can significantly improve the strength and toughness of the material by introducing zirconium oxide / carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler and modified fiber components into the tower material. The synergistic effect of these components enables the tower material to withstand greater wind loads, earthquakes and other external forces, thereby enhancing the stability and safety of the structure. The nano zirconium oxide and carbon fiber are hybridized by silane coupling agent KH-560 to improve the mechanical properties and thermal stability of the tower material, so that the tower material can still maintain excellent performance when subjected to heavy loads and high temperature environments. The in-situ hydrolysis of titanium tetrachloride on the surface of hexagonal boron nitride can enhance the dispersibility of the filler and the interface bonding force with the matrix, thereby improving the material. In order to improve the wear resistance and corrosion resistance of the tower materials, the silane coupling agent KH-550 is used to compositely modify the coconut shell fiber and the glass fiber, which can enhance the strength and toughness of the fiber, thereby improving the compatibility between the fiber and the matrix, and making the tower material more durable. The present invention adopts high-performance nanomaterials and composite modification technology to ensure the strength of the tower material while greatly reducing the weight, which is particularly important for the construction of 5G base stations. It can reduce transportation and installation costs and improve construction efficiency. Moreover, the titanium dioxide modified hexagonal boron nitride filler has good thermal conductivity and chemical stability, which can effectively disperse and conduct the heat generated inside the tower, while resisting the erosion of corrosive environments such as acids and alkalis, and extending the service life of the material.
[0035] 2. The present invention introduces graphene oxide hybrid nanoparticles into the pole tower material, which can not only enhance the mechanical properties of the pole tower material, but also improve its electromagnetic shielding performance, which is particularly important for 5G communication base stations, and can reduce the impact of electromagnetic radiation on the surrounding environment and ensure communication quality. Moreover, through the hybridization of graphene oxide and amino-modified nano-silica particles, the electrical conductivity and thermal conductivity of the pole tower material can be improved, which is beneficial to the transmission and heat dissipation of 5G signals. The components in the present invention are mostly inorganic substances or degradable organic substances, which have good environmental protection performance. After the pole tower reaches the end of its service life, it can be effectively recycled and reused to reduce the impact on the environment. After being blended in an internal mixer, it is pressed and formed, with a simple process and high production efficiency. At the same time, the material has good plasticity and processability, and can be made into pole towers of various shapes and sizes according to actual needs. Secondly, since the prepared pole tower material has the characteristics of light weight, high strength, corrosion resistance, and easy processing, it can significantly reduce the construction and operation costs of 5G base stations, thereby improving economic benefits to a certain extent. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The present invention will be further described below in conjunction with the embodiments.
[0038] Example 1
[0039] A material for a high-performance ultra-thin 5G pole tower in this embodiment, the material for the high-performance ultra-thin 5G pole tower is composed of the following components: zirconium oxide / carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler, modified fiber component, graphene oxide hybrid nanoparticles and polyurethane;
[0040] The zirconium oxide / carbon fiber hybrid powder is prepared by hybridizing nano zirconium oxide and carbon fiber with a silane coupling agent KH-560, wherein the preparation method of the zirconium oxide / carbon fiber hybrid powder is as follows:
[0041] S2.1. Weigh 5 g of nano-zirconia powder and disperse it in 100 mL of anhydrous ethanol. Ultrasonic dispersion is performed at a frequency of 28 kHz for 30 min, and then 30 mL of silane coupling agent KH-560 is added. Stir at a speed of 200 r / min for 6 h in a water bath at 60°C, and then centrifugally wash with 100 mL of anhydrous ethanol. Dry in an oven at 55°C for 3 h, and the obtained product is recorded as modified nano-zirconia powder.
[0042] S2.2. Weigh 0.2g of carbon fiber and disperse it in 100mL of anhydrous ethanol. Ultrasonic disperse it at a frequency of 28kHz for 30min, then add 30mL of silane coupling agent KH-560. Stir it at a speed of 200r / min for 6h in a water bath at 60℃, then add 2g of modified nano-zirconia powder. Continue stirring at the original speed for 6h, wash it by centrifugation with 150mL of anhydrous ethanol, and dry it in an oven at 58℃ for 3h to obtain the zirconia / carbon fiber hybrid powder.
[0043] The titanium dioxide modified hexagonal boron nitride filler is prepared by in-situ hydrolysis of titanium tetrachloride on the surface of hexagonal boron nitride, wherein the preparation method of the titanium dioxide modified hexagonal boron nitride filler is as follows:
[0044] S4.1. Weigh 1g of hexagonal boron nitride and pour it into 20mL of deionized water. Ultrasonic dispersion is carried out at a frequency of 26kHz for 30min, and the dispersion is recorded. Pour 1mL of titanium tetrachloride into 30mL of deionized water, stir magnetically at a speed of 300r / min for 30min, and then add the dispersion. Add 5mol / L sodium hydroxide solution to adjust the pH value to 6, and stir at a speed of 200r / min for 30min. Then pour it into a hydrothermal reactor and heat it to 180℃ for 10h. The obtained product is recorded as the reaction product.
[0045] S4.2. After cooling the reaction product to room temperature, centrifuge it at a speed of 5000r / min for 5 minutes to remove the filtrate. The obtained precipitate is washed with deionized water and anhydrous ethanol in turn, and then placed in an oven at 50°C to dry for 12 hours. After grinding through a 200-mesh sieve, the obtained product is titanium dioxide modified hexagonal boron nitride.
[0046] The modified fiber component is prepared by composite modification of coconut shell fiber and glass fiber by silane coupling agent KH-550, wherein the preparation method of the modified fiber component is as follows:
[0047] S6.1, soak the coconut shell fiber in a 2% sodium hydroxide solution for 1 hour, filter out the filtrate, wash it three times with a 0.5% hydrochloric acid solution, then wash it with deionized water until it is neutral, freeze-dry it, and record it as modified coconut shell fiber;
[0048] S6.2. Weigh 5 mL of silane coupling agent KH-550 and disperse it in 95 mL of anhydrous ethanol to prepare a silane coupling agent dispersion. Then, mix the coconut shell fiber and the glass fiber in an equal weight ratio and record it as mixed fiber. Weigh 30 g of the mixed fiber and add it into 100 mL of the silane coupling agent dispersion. After soaking for 2 hours, filter and remove the filtrate. Place it in an oven at 40°C and dry it for 12 hours to obtain the modified fiber component.
[0049] The graphene oxide hybrid nanoparticles are prepared using graphene oxide and amino-modified nano-silicon dioxide particles as raw materials, wherein the preparation method of the graphene oxide hybrid nanoparticles is as follows:
[0050] S8.1, weigh 72g of anhydrous ethanol, 8g of deionized water and 20g of 3-aminopropyltriethoxysilane into a flask, stir at a speed of 500r / min for 1h, then add 12g of nano-silica and stir at a speed of 500r / min for 1.5h. After the reaction is completed, filter and remove the filtrate and wash with anhydrous ethanol and deionized water three times respectively, place in an oven at 50°C and dry for 2h, then grind through a 200-mesh sieve to obtain amino-modified nano-silica particles;
[0051] S8.2, weigh 1g of graphene oxide and disperse it in 300mL of deionized water to prepare a graphene oxide aqueous solution, then weigh 1g of amino-modified nano-silica particles and disperse them in 500mL of anhydrous ethanol, stir at a speed of 500r / min for 10min, then drip the graphene oxide aqueous solution at a dripping rate of 2 drops / s, ultrasonically disperse at a frequency of 26kHz for 30min, then filter and wash with deionized water and anhydrous ethanol three times, place in an oven at 55°C and dry for 2h, then grind through a 200-mesh sieve, and the obtained particles are recorded as the particles to be hybridized;
[0052] S8.3. Weigh 3 g of the particles to be hybridized and disperse them in 500 mL of deionized water to prepare a suspension. Then, add a sodium borohydride solution with a concentration of 0.1 g / mL to adjust the pH value to 10. Stir at 300 r / min for 2 h in a water bath at 80°C, wash three times with deionized water, centrifuge at 5000 r / min for 5 min, and dry the precipitate in an oven at 55°C for 3 h to obtain graphene oxide hybrid nanoparticles.
[0053] A method for preparing a material for a high-performance ultra-thin 5G tower, the preparation method comprising:
[0054] Weigh 200 parts by weight of polyurethane and pour it into an internal mixer. After heating to 180°C, add 0.5 parts by weight of zirconium oxide / carbon fiber hybrid powder, 0.5 parts by weight of titanium dioxide modified hexagonal boron nitride filler, 1 part by weight of modified fiber component and 0.5 parts by weight of graphene oxide hybrid nanoparticles. After blending, take out and press into shape, and the result is the material for high-performance ultra-thin 5G pole towers.
[0055] Example 2
[0056] A material for a high-performance ultra-thin 5G pole tower in this embodiment, the material for the high-performance ultra-thin 5G pole tower is composed of the following components: zirconium oxide / carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler, modified fiber component, graphene oxide hybrid nanoparticles and polyurethane;
[0057] The zirconium oxide / carbon fiber hybrid powder is prepared by hybridizing nano zirconium oxide and carbon fiber with a silane coupling agent KH-560, wherein the preparation method of the zirconium oxide / carbon fiber hybrid powder is as follows:
[0058] S2.1. Weigh 5 g of nano-zirconia powder and disperse it in 100 mL of anhydrous ethanol. Ultrasonic dispersion is performed at a frequency of 28 kHz for 30 min, and then 30 mL of silane coupling agent KH-560 is added. Stir at a speed of 200 r / min for 6 h in a water bath at 60°C, and then centrifugally wash with 100 mL of anhydrous ethanol. Dry in an oven at 55°C for 3 h, and the obtained product is recorded as modified nano-zirconia powder.
[0059] S2.2. Weigh 0.2g of carbon fiber and disperse it in 100mL of anhydrous ethanol. Ultrasonic disperse it at a frequency of 28kHz for 30min, then add 30mL of silane coupling agent KH-560. Stir it at a speed of 200r / min for 6h in a water bath at 60℃, then add 2g of modified nano-zirconia powder. Continue stirring at the original speed for 6h, wash it by centrifugation with 150mL of anhydrous ethanol, and dry it in an oven at 58℃ for 3h to obtain the zirconia / carbon fiber hybrid powder.
[0060] The titanium dioxide modified hexagonal boron nitride filler is prepared by in-situ hydrolysis of titanium tetrachloride on the surface of hexagonal boron nitride, wherein the preparation method of the titanium dioxide modified hexagonal boron nitride filler is as follows:
[0061] S4.1. Weigh 1g of hexagonal boron nitride and pour it into 20mL of deionized water. Ultrasonic dispersion is carried out at a frequency of 26kHz for 30min, and the dispersion is recorded. Pour 1mL of titanium tetrachloride into 30mL of deionized water, stir magnetically at a speed of 300r / min for 30min, and then add the dispersion. Add 5mol / L sodium hydroxide solution to adjust the pH value to 6, and stir at a speed of 200r / min for 30min. Then pour it into a hydrothermal reactor and heat it to 180℃ for 10h. The obtained product is recorded as the reaction product.
[0062] S4.2. After cooling the reaction product to room temperature, centrifuge it at a speed of 5000r / min for 5 minutes to remove the filtrate. The obtained precipitate is washed with deionized water and anhydrous ethanol in turn, and then placed in an oven at 50°C to dry for 12 hours. After grinding through a 200-mesh sieve, the obtained product is titanium dioxide modified hexagonal boron nitride.
[0063] The modified fiber component is prepared by composite modification of coconut shell fiber and glass fiber by silane coupling agent KH-550, wherein the preparation method of the modified fiber component is as follows:
[0064] S6.1, soak the coconut shell fiber in a 2% sodium hydroxide solution for 1 hour, filter out the filtrate, wash it three times with a 0.5% hydrochloric acid solution, then wash it with deionized water until it is neutral, freeze-dry it, and record it as modified coconut shell fiber;
[0065] S6.2. Weigh 5 mL of silane coupling agent KH-550 and disperse it in 95 mL of anhydrous ethanol to prepare a silane coupling agent dispersion. Then, mix the coconut shell fiber and the glass fiber in an equal weight ratio and record it as mixed fiber. Weigh 40 g of the mixed fiber and add it into 100 mL of the silane coupling agent dispersion. After soaking for 2 hours, filter to remove the filtrate and dry it in an oven at 40°C for 12 hours to obtain the modified fiber component.
[0066] The graphene oxide hybrid nanoparticles are prepared using graphene oxide and amino-modified nano-silicon dioxide particles as raw materials, wherein the preparation method of the graphene oxide hybrid nanoparticles is as follows:
[0067] S8.1, weigh 72g of anhydrous ethanol, 8g of deionized water and 20g of 3-aminopropyltriethoxysilane into a flask, stir at a speed of 500r / min for 1h, then add 15g of nano-silicon dioxide and stir at a speed of 500r / min for 1.5h. After the reaction is completed, filter and remove the filtrate, wash with anhydrous ethanol and deionized water three times respectively, place in an oven at 50°C and dry for 2h, then grind through a 200-mesh sieve to obtain amino-modified nano-silicon dioxide particles;
[0068] S8.2, weigh 1g of graphene oxide and disperse it in 300mL of deionized water to prepare a graphene oxide aqueous solution, then weigh 1g of amino-modified nano-silica particles and disperse them in 500mL of anhydrous ethanol, stir at a speed of 500r / min for 10min, then drip the graphene oxide aqueous solution at a dripping rate of 2 drops / s, ultrasonically disperse at a frequency of 26kHz for 30min, then filter and wash with deionized water and anhydrous ethanol three times, place in an oven at 55°C and dry for 2h, then grind through a 200-mesh sieve, and the obtained particles are recorded as the particles to be hybridized;
[0069] S8.3. Weigh 3 g of the particles to be hybridized and disperse them in 500 mL of deionized water to prepare a suspension. Then, add a sodium borohydride solution with a concentration of 0.1 g / mL to adjust the pH value to 12. Stir at 300 r / min for 2 h in a water bath at 80°C, wash three times with deionized water, centrifuge at 5000 r / min for 5 min, and dry the precipitate in an oven at 55°C for 3 h to obtain graphene oxide hybrid nanoparticles.
[0070] A method for preparing a material for a high-performance ultra-thin 5G tower, the preparation method comprising:
[0071] Weigh 200 parts by weight of polyurethane and pour it into an internal mixer. After heating to 190°C, add 1 part by weight of zirconium oxide / carbon fiber hybrid powder, 1 part by weight of titanium dioxide modified hexagonal boron nitride filler, 2 parts by weight of modified fiber components and 1 part by weight of graphene oxide hybrid nanoparticles. After blending, take out and press into shape, and the result is the material for high-performance ultra-thin 5G pole towers.
[0072] Example 3
[0073] A material for a high-performance ultra-thin 5G pole tower in this embodiment, the material for the high-performance ultra-thin 5G pole tower is composed of the following components: zirconium oxide / carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler, modified fiber component, graphene oxide hybrid nanoparticles and polyurethane;
[0074] The zirconium oxide / carbon fiber hybrid powder is prepared by hybridizing nano zirconium oxide and carbon fiber with a silane coupling agent KH-560, wherein the preparation method of the zirconium oxide / carbon fiber hybrid powder is as follows:
[0075] S2.1. Weigh 5 g of nano-zirconia powder and disperse it in 100 mL of anhydrous ethanol. Ultrasonic dispersion is performed at a frequency of 28 kHz for 30 min, and then 30 mL of silane coupling agent KH-560 is added. Stir at a speed of 200 r / min for 6 h in a water bath at 60°C, and then centrifugally wash with 100 mL of anhydrous ethanol. Dry in an oven at 55°C for 3 h, and the obtained product is recorded as modified nano-zirconia powder.
[0076] S2.2. Weigh 0.2g of carbon fiber and disperse it in 100mL of anhydrous ethanol. Ultrasonic disperse it at a frequency of 28kHz for 30min, then add 30mL of silane coupling agent KH-560. Stir it at a speed of 200r / min for 6h in a water bath at 60℃, then add 2g of modified nano-zirconia powder. Continue stirring at the original speed for 6h, wash it by centrifugation with 150mL of anhydrous ethanol, and dry it in an oven at 58℃ for 3h to obtain the zirconia / carbon fiber hybrid powder.
[0077] The titanium dioxide modified hexagonal boron nitride filler is prepared by in-situ hydrolysis of titanium tetrachloride on the surface of hexagonal boron nitride, wherein the preparation method of the titanium dioxide modified hexagonal boron nitride filler is as follows:
[0078] S4.1. Weigh 1g of hexagonal boron nitride and pour it into 20mL of deionized water. Ultrasonic dispersion is carried out at a frequency of 26kHz for 30min, and the dispersion is recorded. Pour 1mL of titanium tetrachloride into 30mL of deionized water, stir magnetically at a speed of 300r / min for 30min, and then add the dispersion. Add 5mol / L sodium hydroxide solution to adjust the pH value to 6, and stir at a speed of 200r / min for 30min. Then pour it into a hydrothermal reactor and heat it to 180℃ for 10h. The obtained product is recorded as the reaction product.
[0079] S4.2. After cooling the reaction product to room temperature, centrifuge it at a speed of 5000r / min for 5 minutes to remove the filtrate. The obtained precipitate is washed with deionized water and anhydrous ethanol in turn, and then placed in an oven at 50°C to dry for 12 hours. After grinding through a 200-mesh sieve, the obtained product is titanium dioxide modified hexagonal boron nitride.
[0080] The modified fiber component is prepared by composite modification of coconut shell fiber and glass fiber by silane coupling agent KH-550, wherein the preparation method of the modified fiber component is as follows:
[0081] S6.1, soak the coconut shell fiber in a 2% sodium hydroxide solution for 1 hour, filter out the filtrate, wash it three times with a 0.5% hydrochloric acid solution, then wash it with deionized water until it is neutral, freeze-dry it, and record it as modified coconut shell fiber;
[0082] S6.2. Weigh 5 mL of silane coupling agent KH-550 and disperse it in 95 mL of anhydrous ethanol to prepare a silane coupling agent dispersion. Then, mix the coconut shell fiber and the glass fiber in an equal weight ratio and record it as mixed fiber. Weigh 35 g of the mixed fiber and add it into 100 mL of the silane coupling agent dispersion. After soaking for 2 hours, filter and remove the filtrate. Place it in an oven at 40°C and dry it for 12 hours to obtain the modified fiber component.
[0083] The graphene oxide hybrid nanoparticles are prepared using graphene oxide and amino-modified nano-silicon dioxide particles as raw materials, wherein the preparation method of the graphene oxide hybrid nanoparticles is as follows:
[0084] S8.1, weigh 72g of anhydrous ethanol, 8g of deionized water and 20g of 3-aminopropyltriethoxysilane into a flask, stir at a speed of 500r / min for 1h, then add 13g of nano-silicon dioxide and stir at a speed of 500r / min for 1.5h. After the reaction is completed, filter and remove the filtrate and wash with anhydrous ethanol and deionized water three times respectively, place in an oven at 50°C and dry for 2h, then grind through a 200-mesh sieve to obtain amino-modified nano-silicon dioxide particles;
[0085] S8.2, weigh 1g of graphene oxide and disperse it in 300mL of deionized water to prepare a graphene oxide aqueous solution, then weigh 1g of amino-modified nano-silica particles and disperse them in 500mL of anhydrous ethanol, stir at a speed of 500r / min for 10min, then drip the graphene oxide aqueous solution at a dripping rate of 2 drops / s, ultrasonically disperse at a frequency of 26kHz for 30min, then filter and wash with deionized water and anhydrous ethanol three times, place in an oven at 55°C and dry for 2h, then grind through a 200-mesh sieve, and the obtained particles are recorded as the particles to be hybridized;
[0086] S8.3. Weigh 3 g of the particles to be hybridized and disperse them in 500 mL of deionized water to prepare a suspension. Then, add a sodium borohydride solution with a concentration of 0.1 g / mL to adjust the pH value to 11. Stir at 300 r / min for 2 h in a water bath at 80°C, wash three times with deionized water, centrifuge at 5000 r / min for 5 min, and dry the precipitate in an oven at 55°C for 3 h to obtain graphene oxide hybrid nanoparticles.
[0087] A method for preparing a material for a high-performance ultra-thin 5G tower, the preparation method comprising:
[0088] Weigh 200 parts by weight of polyurethane and pour it into an internal mixer. After heating to 185°C, add 0.8 parts by weight of zirconium oxide / carbon fiber hybrid powder, 0.7 parts by weight of titanium dioxide modified hexagonal boron nitride filler, 2 parts by weight of modified fiber components and 0.8 parts by weight of graphene oxide hybrid nanoparticles. After blending, take out and press into shape, and the result is the material for high-performance ultra-thin 5G pole towers.
[0089] Comparative Example 1
[0090] The material and preparation method of a high-performance ultra-thin 5G pole tower provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the zirconium oxide / carbon fiber hybrid powder in Example 1 is replaced with carbon fiber.
[0091] Comparative Example 2
[0092] The material and preparation method of a high-performance ultra-thin 5G pole tower provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the titanium dioxide-modified hexagonal boron nitride filler in Example 1 is replaced with nano titanium dioxide.
[0093] Comparative Example 3
[0094] The material and preparation method of a high-performance ultra-thin 5G pole tower provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified fiber component in Example 1 is replaced with glass fiber.
[0095] Performance Testing
[0096] The materials of the high-performance ultra-thin 5G pole towers prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-3 is tested. The specific testing methods and test items are as follows:
[0097] 1. The impact properties of Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard of GB / T1043.1-2008, with the pendulum speed being 3.5 m / s. The obtained data are recorded in the following table;
[0098] 2. The bending strength of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T1449-2005, and the obtained data are recorded in the following table;
[0099] 3. The salt spray resistance of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard test of GB / T1771-1991, and the obtained data were recorded in the following table;
[0100] 4. The friction performance of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard test of GB / T3960-1983, and the obtained data were recorded in the following table;
[0101]
[0102] It can be seen from the data in the above table that the mechanical properties, corrosion resistance and wear resistance of the materials of the high-performance ultra-thin 5G tower in Examples 1-3 are significantly better than those of Comparative Examples 1-3, indicating that the addition of zirconium oxide / carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler and modified fiber components to the tower material can improve the mechanical properties, corrosion resistance and wear resistance of the tower material. In summary, the material performance of the high-performance ultra-thin 5G tower prepared in the present invention is more excellent and has excellent market application prospects.
[0103] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0104] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-performance ultra-thin 5G tower material, characterized in that: The material of the high-performance ultra-thin 5G pole tower is composed of the following components: zirconium oxide / carbon fiber hybrid powder, titanium dioxide modified hexagonal boron nitride filler, modified fiber component, graphene oxide hybrid nanoparticles and polyurethane; The zirconium oxide / carbon fiber hybrid powder is prepared by hybridizing nano zirconium oxide and carbon fiber with a silane coupling agent KH-560; The titanium dioxide modified hexagonal boron nitride filler is prepared by in-situ hydrolysis of titanium tetrachloride on the surface of hexagonal boron nitride; The modified fiber component is prepared by composite modification of coconut shell fiber and glass fiber by silane coupling agent KH-550; The graphene oxide hybrid nanoparticles are prepared using graphene oxide and amino-modified nano-silicon dioxide particles as raw materials; The preparation method of the zirconium oxide / carbon fiber hybrid powder is: S2.1, weigh 5g of nano zirconium oxide powder and disperse it in 100mL of anhydrous ethanol, add 30mL of silane coupling agent KH-560 after ultrasonic treatment, stir at 200r / min for 6h in a water bath at 60℃, wash by centrifugation with anhydrous ethanol, and dry to obtain the modified nano zirconium oxide powder; S2.2, weigh 0.2g of carbon fiber and disperse it in 100mL of anhydrous ethanol, add 30mL of silane coupling agent KH-560 after ultrasonic treatment, stir at 200r / min for 6h in a water bath at 60℃, add 2g of modified nano zirconium oxide powder, continue stirring at the original speed for 6h, wash with anhydrous ethanol by centrifugation, and dry to obtain zirconium oxide / carbon fiber hybrid powder; The preparation method of the titanium dioxide modified hexagonal boron nitride filler is: S4.
1. Weigh 1g of hexagonal boron nitride and pour it into 20mL of deionized water. After ultrasonic treatment, record it as dispersion. Pour 1mL of titanium tetrachloride into 30mL of deionized water, stir magnetically for 30min, then add the dispersion. Add sodium hydroxide solution dropwise to adjust the pH value to 6, stir and react for 30min, then pour it into a hydrothermal reactor and heat it to 180℃ for 10h. The result is recorded as reaction product. S4.2, cooling the reaction product to room temperature and centrifuging to remove the filtrate, washing the obtained precipitate with deionized water and anhydrous ethanol in turn, drying it in an oven at 50°C for 12 hours, and grinding it through a 200-mesh sieve to obtain titanium dioxide-modified hexagonal boron nitride; The preparation method of the modified fiber component is: S6.1, soaking the coconut shell fiber in a sodium hydroxide solution for 1 hour, filtering and removing the filtrate, washing with a hydrochloric acid solution for 3 times, and then washing with deionized water until neutral, freeze-drying, and recording the result as modified coconut shell fiber; S6.2, weigh 5 mL of silane coupling agent KH-550 and disperse it in 95 mL of anhydrous ethanol to prepare a silane coupling agent dispersion, then mix coconut shell fiber and glass fiber in an equal weight ratio and record it as mixed fiber, weigh 30-40 g of mixed fiber and add it into 100 mL of silane coupling agent dispersion, soak for 2 hours, filter and remove the filtrate, and dry the obtained modified fiber component; The preparation method of the graphene oxide hybrid nanoparticles is: S8.1, weigh 72g of anhydrous ethanol, 8g of deionized water and 20g of 3-aminopropyltriethoxysilane into a flask, stir and mix, then add 12-15g of nano-silica and stir to react, after the reaction is completed, filter and remove the filtrate, wash with anhydrous ethanol and deionized water three times respectively, dry and grind through a 200 mesh sieve to obtain the amino-modified nano-silica particles; S8.2, weigh 1g of graphene oxide and disperse it in 300mL of deionized water to prepare a graphene oxide aqueous solution, then weigh 1g of amino-modified nano-silica particles and disperse them in 500mL of anhydrous ethanol, and drop the graphene oxide aqueous solution after uniform dispersion, and then use deionized water and anhydrous ethanol to filter and wash three times after ultrasonic treatment, and then grind through a 200-mesh sieve after drying, and the obtained particles are recorded as the particles to be hybridized; S8.
3. Weigh 3 g of the particles to be hybridized and disperse them in 500 mL of deionized water to prepare a suspension. Then, add a 0.1 g / mL sodium borohydride solution to adjust the pH value to 10-12. After stirring the reaction in a water bath at 80°C, wash it three times with deionized water. After centrifugal drying, the resulting product is graphene oxide hybrid nanoparticles.
2. The material of a high-performance ultra-thin 5G tower according to claim 1, characterized in that: The operating method of ultrasonic treatment in S2.1 is ultrasonic dispersion at a frequency of 28 kHz for 30 min, the amount of anhydrous ethanol used for centrifugal washing in S2.1 is 100 mL, the operating method of drying treatment in S2.1 is drying in an oven at 55°C for 3 h, the operating method of ultrasonic treatment in S2.2 is ultrasonic dispersion at a frequency of 28 kHz for 30 min, the amount of anhydrous ethanol used for centrifugal washing in S2.2 is 150 mL, and the operating method of drying treatment in S2.2 is drying in an oven at 58°C for 3 h.
3. The material of a high-performance ultra-thin 5G tower according to claim 1, characterized in that: The operation method of ultrasonic treatment in S4.1 is ultrasonic dispersion at a frequency of 26kHz for 30 minutes, the rotation speed of magnetic stirring in S4.1 is 300r / min, the concentration of sodium hydroxide solution in S4.1 is 5mol / L, the rotation speed of stirring reaction in S4.1 is 200r / min, and the operation method of centrifugal treatment in S4.2 is centrifugation at a rotation speed of 5000r / min for 5 minutes.
4. The material of a high-performance ultra-thin 5G tower according to claim 1, characterized in that: The mass concentration of the sodium hydroxide solution in S6.1 is 2%, the mass concentration of the hydrochloric acid solution in S6.1 is 0.5%, and the operation method of the drying treatment in S6.2 is to place it in an oven at 40°C and dry it for 12 hours.
5. The material of a high-performance ultra-thin 5G tower according to claim 1, characterized in that: The stirring and mixing operation method in S8.1 is stirring at a speed of 500r / min for 1h, the stirring reaction operation method in S8.1 is stirring at a speed of 500r / min for 1.5h, the drying treatment operation method in S8.1 is drying in an oven at 50°C for 2h, the uniform dispersion operation method in S8.2 is stirring at a speed of 500r / min for 10min, the dripping rate in S8.2 is 2 drops / s, the ultrasonic treatment operation method in S8.2 is ultrasonic dispersion at a frequency of 26kHz for 30min, the drying treatment operation method in S8.2 is drying in an oven at 55°C for 2h, the stirring reaction operation method in S8.3 is stirring at a speed of 300r / min for 2h, and the centrifugal drying operation method in S8.3 is first centrifuging at a speed of 5000r / min for 5min and then drying the precipitate in an oven at 55°C for 3h.
6. A method for preparing a material for a high-performance ultra-thin 5G tower according to any one of claims 1 to 5, characterized in that: The preparation method is: Weigh 200 parts by weight of polyurethane and pour it into an internal mixer. After heating to 180-190°C, add 0.5-1 parts by weight of zirconium oxide / carbon fiber hybrid powder, 0.5-1 parts by weight of titanium dioxide modified hexagonal boron nitride filler, 1-2 parts by weight of modified fiber components and 0.5-1 parts by weight of graphene oxide hybrid nanoparticles. After blending, take out and press into shape, and the result is the material for high-performance ultra-thin 5G pole towers.
